A study of the safety and immunogenicity of a new vaccine for the prevention of COVID-19 based on virus-like particles in phase I clinical trials - Tatiana V. Grebennikova; Olga N. Zaykova; Alexey A. Plotnikov; Lyudmila V. Kostina; Yana Yu. Chernoryzh; Olesia V. Eliseeva; Oleg E. Latyshev; Viktor F. Larichev; Irina T. Fedyakina; Milana A. Losich; Ilya M. Kirillov; Ilya E. Filatov; et al. (Журнал микробиологии, эпидемиологии и иммунобиологии, 2025)
Introduction. One of the more promising developments in preventing the spread of infections, including COVID-19, is the production of vaccines based on virus-like particles (VLP). Currently, in the National Research Center for Epidemiology and Microbiology named after N.F. Gamaleya of the Ministry of Health of the Russia has developed a VLP-based vaccine against COVID-19.